BIOCHEMICAL FINDINGS IN THE EJACULATE OF MEN WITH NON-OBSTRUCTIVE AZOOSPERMIA - Bartek, Josef; Sobek, Aleš; Hrbková, Kamila; Mucha, Zdeněk; Záťura, František; Psotová, Jitka (Biomedical papers, 1998)
In men with non-obstructive azoospermia, testicle biopsy can provide isolated sperm which can be used for fertilization ofan oocyte. The male seminal plasma was examined for adequate biochemical parameters and then tested as potentialdiagnostic parameters for prediction of sperm presence in non-obstructive azoospermia. Sperm was obtained by preparationof the testicular tissue. Biochemical parameters in men with found sperm were compared to findings obtained from menwithout sperm in the testicular tissue. The following parameters were analysed: fructose, lactate dehydrogenase, total acidphosphatase, Zn, K, Na, Cl, pH. No statistically significant differences were found in both groups under study. Biochemicalexamination of the ejaculate cannot provide any prediction of sperm retrieval in non-obstructive azoospermia.
Keywords: Non-obstructive azoospermia/ Prediction of sperm retrieval / Biochemical findings in the ejaculate